All-aromatic SWCNT-Polyetherimide nanocomposites for thermal energy harvesting applications. (1st March 2018) - Tzounis, Lazaros; Hegde, Maruti; Liebscher, Marco; Dingemans, Theo; Pötschke, Petra; Paipetis, Alkiviadis S.; Zafeiropoulos, Nikolaos E.; Stamm, Manfred
Abstract: The thermoelectric properties of amorphous and semi-crystalline high-performance polyetherimide–SWCNT nanocomposites are reported for the first time. Nanocomposites based on a non-linear polyetherimide (PEI) model system, labeled aBPDA-P3, with 0.6, 4.4 and 10 vol% SWCNTs remained amorphous after the addition of SWCNTs. In contrast, SWCNTs induced crystallization in a linear PEI model system labeled as ODPA-P3. The (thermo)mechanical properties were fully characterized using thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMTA). The electrical conductivity was studied by four-probe measurements and showed higher values for the ODPA-P3 films reaching 20 S/m at 10 vol% of SWCNTs. The thermoelectric performance revealed by Seebeck coefficient ( S ) measurements showed values of 40 and 55 μV/K for the 0.6 and 4.4 vol% ODPA-P3 SWCNT nanocomposites, while 16 and 47 μV/K for aBPDA-P3 amorphous films. This enhancement has been attributed to SWCNT–induced crystallization in ODPA-P3 matrix. The PEI-SWCNT nanocomposites are ideal candidates as organic flexible films and coatings for large area thermal energy harvesting, where high temperature gradients exist. Potential applications can be envisaged in the aerospace, automotive and micro-electronics sectors.